Delay Estimation in Networks with Cooperative Arrival Dynamics - O. А. Markelov; N. S. Tymchenko; M. I. Bogachev (Известия высших учебных заведений России: Радиоэлектроника, 2025)
Introduction. Modern complex systems with a network structure are characterized by spatial and temporal long-term dependence of flows. The existing models of mass service theory based on the assumptions of stationarity and mutual statistical independence of fluctuations in the intensity of incoming flows significantly underestimate real delays.Aim. Development of an improved model for estimation of aggregated traffic delays in highly loaded networks taking into account statistical characteristics of interrelations between activity fluctuations in nodes and channels of the network.Materials and methods. A superstatistical approach is applied to analytically correct the Kingman formula for estimating the waiting time based on the calculation of the coefficients of variation of arrival intensities and mutual correlations between the intensities of the traffic generated by different nodes. Analytically obtained approximations of probability densities of delay distribution by q-exponential distributions are used to estimate the characteristics of aggregated traffic, the results of which are confirmed by the data of simulation modeling of aggregated traffic. In addition, the validation of the proposed estimations is performed on the example of analyzing empirical traffic data of the MAWI academic backbone network. The duration of the analyzed time segments of the traffic was adapted to adequately compare the results for model and empirical data, with integral statistics constructed based on the results of the analysis of several full-day records.Results. An analytical model for estimating delays in aggregated traffic was developed, taking into account the coefficients of variation of arrival intensities and mutual correlations of traffic intensities originating from different nodes in the network. The analytical estimation of delay distribution was shown to give an intermediate result between the estimations obtained by using two modeling schemes, which is caused by the prevalence of errors of discreteness or finiteness of data sampling depending on the modeling scheme.Conclusion. The application of the superstatistical approach to account for statistical interrelationships allows the estimates of delay times in highly loaded networks to be clarified on the basis of substituting the adjusted characteristics of aggregated traffic into the Kingman formula, thus providing more detailed estimates of delays in complex engineering systems with a network structure.